A STUDY ON LANGUAGE ASSESSMENT APPLIED BY ENGLISH TEACHER - Septika Septika; Kurniati Kurniati (INOVISH JOURNAL, 2017)
Abstract The purpose of this research was to investigate how the English teachers of Junior High School 4 Banjit, Way Kanan apply language assessment in teaching learning process. This study used descriptive qualitative method. The respondent is one of English teachers of that school. For collecting the data, the researcher employed observationand interview. The finding showed that the participant tend to less care toward assessment. It is caused by less of knowledge about the assessment itself. The participant was reluctant did the assessment because he felt that it is difficult to be conducted and complex matter. In conclusion the participant did not assess optimally and the assessments applied by the teacher were less able to present the result of students’ learning.  Key Words:  language, assessment, students’learning.